Družboslovna informatika - Petrič, Gregor (Teorija in praksa, 2013)
Social informatics as a scientific field lies at the crossroads between investigations of information and communication technology (ICT) as an informatics and methodological tool and a study of ICT as an object of social scientific analyses. This article argues for the convergence between the Slovenian research tradition of social informatics and other paradigmatic-geographical traditions on the levels of conceptualisation, research areas and methodology. Moreover, convergence is not only found within the scientific community of social informatics, but is also present on the level of its disciplinary relations with other scientific fields. Both levels of convergence suggest many possibilities and the great potential of the further development of the Slovenian tradition, as well as for the social and scientific relevance of social informatics.
Keywords: Communication technology; Družboslovna metodologija; Družboslovno raziskovanje; Fakulteta za družbene vede; Informacijska tehnologija; Informatics; Informatika; information science; Information technology; Komunikacijska tehnologija; Science; Slovenia; Slovenija; Social science methodology; Social science research; Znanost